Experimental Study on the Development Characteristics and Controlling Factors of Microscopic Organic Matter Pore and Fracture System in Shale - Zhang, Qin; Liu, Zaiyang; Liu, Chang; Zhu, Xiaomin; Steel, Ronald J.; Tian, Hanyun; Wang, Kai; Song, Zeping (Frontiers in Earth Science, 2021)
Research on microscopic pore and fracture system of shale is a hot spot in the field of unconventional petroleum geology. Micro- and nano-scale organic matter pores in shale play a vital role in the accumulation of hydrocarbons. Research on the types, evolution rules and controlling factors of organic matter pore-fracture system in shale reservoirs can provide scientific guidance for the prediction of shale “sweet spots”. In this paper, taking the shales from the Napo Formation, Oriente Basin, the Shahejie Formation, Zhanhua Sag, Bohai Bay Basin, and the Longmaxi and Wufeng Formations, Sichuan Basin as an example, the developmental characteristics of organic matter pore-fracture system were systematically studied using thin section, argon ion profiling scanning electron microscopy, X-ray diffraction, N2 adsorption and desorption, geochemistry experiments, and image processing technology. The types of shale organic matter pores were divided into kerogen-hosted pores, organic matter microfractures (intra-organic matter and organic matter edge microfractures), and asphalt pores (or intra-asphalt pores). The circumferences of organic pore were generally within 100 nm, and the areas of most pores were smaller than 1,000 nm2. Face rates of the organic pores were generally less than 1.5%, and the proportion of shale samples with a shape factor of 1 reached more than 50%. In addition, the deviation angles of organic matter pores at (0°, 45°) reached 90%, which showed that most of the organic matter pores tended to be oriented pores. The increase in the degree of thermal evolution provided driving force for the formation of circular pores in the organic matter. Internal factors (abundance of organic matter, kerogen types, and maturity) and external factors (diagenesis and mineral composition) controled the development of shale organic matter pores. Maturity, TOC content and inorganic minerals such as clay and pyrite content were positively correlated with the development of organic matter pores. However, brittle minerals caused a decrease in the face ratio of organic matter pores. Diagenetic compaction caused the organic matter pores being deformed or eventually disappeared. This research can provide scientific guidance for the high-efficiency exploration of hydrocarbons in shale.